Integrated Analysis of DNA Methylation and mRNA Expression Profiles to Identify Key Genes in Severe Oligozoospermia - Li, Zhiming; Zhuang, Xuan; Zeng, Jinxiong; Tzeng, Chi-Meng (Frontiers in Physiology, 2017)
Severe oligozoospermia (SO) is a complex disorder, whose etiology is the combined effect of genetic factors and epigenetic conditions. In this study, we examined DNA methylation and mRNA expression status in a set of testicular tissues of SO patients (n=3), and compared methylated data with those derived from obstructive azoospermia (OA) patients (n=3) with normal spermatogenesis phenotype. We identified 1960 differentially methylated CpG sites showing significant alterations in SO versus OA using the Illumina Infinium HumanMethylation450 bead array. By integrating above DNA methylation data and mRNA expression results, we totally identified 72 methylated CpG sites located in 65 genes with anti-correlation between DNA methylation and mRNA expression. Integrated pathways analysis indicates that these genes are involved in response to hormone stimulus, activation of protein kinase activity, and apoptotic process, among others. We also observed some genes with inversely correlated difference is novel in male infertility field, including PTPRN2, EPHX1, SERPINB9, SLIT3, etc. Our results lay a groundwork for further biological study of SO. Moreover, we generated a workflow for integrated analysis of DNA methylation and mRNA expression, which is expandable to other study types.